EFL students’ strategies in learning grammar online - Nadya Irdani; Nur Fatimah; Arilia Triyoga (Universitas Ahmad Dahlan, 2022)
Students' learning strategies are part of teaching and learning success concerns, including in the online grammar class. The research objectives are to describe students' strategies in learning grammar through online grammar classes and to find out the students' problems and solutions in learning grammar online. This research is mixed-method where the data are collected through questionnaires and interviews. One hundred twenty-three students completed the questionnaire, and twelve students were involved in the interview sessions. All respondents are from the English Education Department. The result shows that the students used all learning strategies; memory, cognitive, compensation, metacognitive, affective, and social strategies). However, the highest percentage of the learning strategy employed by the students is cognitive strategies (18.30%), while the least is affective strategies (14.76%). Moreover, students learning grammar online face various problems; an unstable internet connection, having no friends to practice together, difficulty in vocabulary, the lecturer's teaching methods, and punctuality issues.